Oboczność mię cię się // mie cie sie w Księgach o gospodarstwie Piotra Krescentyna z 1549 roku - Osiewicz, Marek (Wydawnictwo „Poznańskie Studia Polonistyczne” i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The goal of this article is to provide a detailed description of the mię cię się // mie cie sie alternation as presented in Księgi o gospodarstwie from 1549. In the analysis, four aspects have been taken into consideration: 1) the alternation’s position range, 2) the textual lack of continuity of the alternation’s state, 3) identification of the extent to which a compositor affected a text, 4) the extent of normalization of the mię cię się // mie cie sie opposition in all identified parts of the text against the background of other texts from the time under scrutiny. In the text, the variants were reflected only in the forms of the się reflexive pronoun. A majority of the text is evidence of a status typical of Krakow prints from the first half of the 16th century referred to as the Lesser Poland standard: a verb + sie, a preposition + się. A different status is confirmed in the initial columns of the book: adjacent to a verb – columns 113–248, following the w, przed, na and nad prepositions – columns 48–78, following the za preposition – columns 1–112. This alternation is most diversified with respect to the text when it accompanies a verb. The distribution of modes of marking the forms of the reflexive pronoun provides evidence that this phenomenon could be affected by the compositor.
The mię cię się // mie cie sie alternation in Księgi o gospodarstwie by Piotr Krescentyn from 1549
Keywords: Polish language in the 16th century; historical phonetics; linguistic variants; linguistic standard; 16th century prints